A multi-scale approach for estimating gradient from volumetric data. - Belaton, Bahari (Universiti Sains Malaysia, 2015)
Gradient is mostly used to approximate a quantity called normal vector, which is widely used in techniques such as raycasting or shading to calculate the shade of a pixel. Central Different Equation (CDE), Forward Difference Equation (FDE) and Backward Difference Equation (BDE) [1] are examples of common finite-difference gradient filters to estimate gradient from discrete data.